DINAMIKA PERKEMBANGAN SEMI PATUNG (TIGA DIMENSIONAL) DI BALI - I Wayan Seriyoga Parta (Ars: Jurnal Seni Rupa dan Desain, 2008)
Sculpture in Pali was a part o f the departed spirit worship transformation practiced from thepre- history time until the coming o f the Hinduism & Buddhism and Chinese culture. At its early stage,sculpture was the materialization o f Gods in the Hindu belief placed in Pur a (house o f worship in Hindureligion) It became the fetus o f the Pali traditional sculpture that held its own fashions and rules. The nextphase ziyis the emergence o f the autodidact artists who mastered these fashions and rules. In their careercourses, they developed a new form o f sculpture that disobeyed them: This new form then appreciatedas a novel creativity which by many art observers defined as 'modern' sculpture. It ivas an assimilationo f the local values and the Western influence carried by Western artists and cultural observers to Bali.Even though it was stagnant once, Bali sculpture moved forward along tlte time dynamics. The youngartists coming from the academic world pioneered further development which led this art branch to thecontemporary art progression. The statues created were experimental, not only seen from the media andmaterial, but also from the ideas and thoughts underlying them which were represented in installation andmultimedia arts. That is why Pali sculpture has been developing dynamically up to now.Keyzvords: sculpture, Hindu, traditional, religious, modern, contemporary, and experimental